Duodenal Stromal Tumor - PEREK, Sadık; PEREK, Asiye; ŞARMAN, Kemal; ERENLER KILIÇ, İlknur; ANDİCAN, A. Ahad (Cerrahpaşa Medical Journal, 2014)
Tumors of the duodenum are uncommon, and benign tumors are much rare. Overall 20-30% of gastrointestinal stromal tumors occur in the small bowel and about one third of these arise in the duodenum. The most common presentation is upper gastrointestinal bleeding, abdominal mass and pain. Immunohistochemical analysis is important in the diagnosis and differantial diagnosis of these tumors. They express CD 34 and CD 117 positivity. Here we report the case of a patient who applied with melena, that was diagnosed as due to the gastrointestinal stromal tumor located between the second and third portion of the duodenum, and managed by wedge resection and primary suture.